Constraints to graduate employment in the City of Johannesburg, South Africa - Edayi, Juliet (My University, 2016)
Graduate unemployment has become a significant factor in the global economy. The economic system now relies on institutional unemployment figures as the indices of the socio-economic well-being of any country. Research shows that graduate unemployment is potentially damaging to the economy. If such unemployment persists, it may lead to the erosion and outdating of graduates' skills–bases, which will affect the economy in the long term. Statistical reports show that there is high graduate unemployment in South Africa; hence graduates struggle to find work despite the skills shortage in the country. This seems to contradict previous studies suggesting that the higher a person‘s education level, the higher his or her probability of finding employment. As a result of the significant rise in unemployment rates among South Africa‘s stock of graduates, the extent of the emerging skills-mismatch possessed by new graduate labour market entrants are increasingly misaligned with the skills demanded by employers.
Thesis (M.Com. (Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2016.
Keywords: College graduates--Employment--South Africa; Unemployment--South Africa; Labor market--South Africa